2008
DOI: 10.1016/j.jasms.2008.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of protein sensitivity for MALDI imaging mass spectrometry after chemical treatment of tissue sections

Abstract: MALDI imaging mass spectrometry (IMS) has become a valuable tool for the investigation of the content and distribution of molecular species in tissue specimens. Numerous methodological improvements have been made to optimize tissue section preparation and matrix deposition protocols, as well as MS data acquisition and processing. In particular for proteomic analyses, washing the tissue sections before matrix deposition has proven useful to improve spectral qualities by increasing ion yields and the number of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
264
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 267 publications
(271 citation statements)
references
References 50 publications
5
264
0
2
Order By: Relevance
“…M atrix-assisted laser desorption/ionization mass spectrometric imaging (MALDI-MSI) was introduced in 1997 [1] and has been widely presented as a powerful method for imaging large [2][3][4][5][6][7][8][9][10][11][12][13][14] and small molecules [15][16][17][18][19][20][21][22][23][24] in tissue. The technique has been applied to a diverse range of applications but there has been particular interest in evaluating opportunities in disease state profiling.…”
Section: Introductionmentioning
confidence: 99%
“…M atrix-assisted laser desorption/ionization mass spectrometric imaging (MALDI-MSI) was introduced in 1997 [1] and has been widely presented as a powerful method for imaging large [2][3][4][5][6][7][8][9][10][11][12][13][14] and small molecules [15][16][17][18][19][20][21][22][23][24] in tissue. The technique has been applied to a diverse range of applications but there has been particular interest in evaluating opportunities in disease state profiling.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that washing the tissue sections with organic solvents such as chloroform and EtOH before matrix deposition increases the number and intensities of protein signals up to 20 kDa [27][28][29]. To test if the increased high mass sensitivity and charge capacity of the high mass HM1 detector may benefit imaging MS of higher mass proteins, mouse brain tissue sections were washed with chloroform and ethanol, prepared with a matrix solution of 20 mg/mL SA in AcN:0.1% TFA (7:3, vol/vol), and then analyzed using an AutoFlex III MALDI-ToF equipped with an MCP and a HM1 detector.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, alcohol was employed to remove salts, lipids, and any other component that would interfere with spectral analyses of biological specimens [18,19]. Additionally, Seeley et al also reported that alcohol-based washes, in particular isopropanol, are the most effective for protein analysis in a MALDI imaging as they effectively remove lipids from biological specimens [20]. Therefore, using alcohols seemed to be one of the ideal choices for better extraction of molecules, especially lipids that are major constituents of cell membranes.…”
Section: Solvent Selection For Lipid Analysismentioning
confidence: 99%